Wedang Uwuh; A Natural Antioxidant from Yogyakarta - Michelle Amanda Lau; Batara Krisnawan Suseno; Susana Elya Sudradjat (Jurnal MedScientiae, 2022)
Natural antioxidants are still favoured due to their high benefits and safety compared to synthetic ones. Wedang uwuh is one example of a traditional drink consisting of various spices (cinnamon, cloves, cardamom, sappanwood, nutmeg, and ginger) rich in antioxidants. This study aimed to determine the optimum infusion method of ready to drink wedang uwuh to achieve its maximum antioxidant potential. Two groups of wedang uwuh samples (grounded and ungrounded) were infused in hot water (90ºC) using tea bags in different timings (1, 3, 5, 10, and 15 minutes). Then their antioxidant activity was measured using the DPPH (2,2-diphenyl-1-picrylhydrazyl) scavenging assay method. The results showed the highest when we infused grounded wedang uwuh for 15 minutes with the IC50 value of 7.97 µg/mL. The smaller the particle size and the longer the infusion time yields lower IC50 value, thus achieving more potent antioxidant activity.